Identifikasi Waste Menggunakan Waste Assessment Model (WAM) di Warehouse Raw Material PT. XYZ - Naziihah, Afifah; Arifin, Jauhari; Nugraha, Billy (Jurnal Media Teknik dan Sistem Industri, 2022)
Warehouse of Raw Materials in PT. XYZ show an increase in the storage of the good, if is not offset by good performance, then the goods will be experiencing delays in handling. This study aims to identify the waste that occurs in the Warehouse of Raw Materials in PT. XYZ. The focus Â of this research is to identify the 7 wastes in the Warehouse raw materials with the lean manufacturing approach using the method of Waste Assessment Model (WAM). The process of waste identification is performed by using Seven Waste Relationship, Waste Relationship Matrix (WRM) and Waste Assessment Questionnaire (WAQ) later in the analysis using a Fishbone Diagram to determine the root cause of the problem so we get the proposal improves then the priority of the improvement obtained by using the table of priorities that is done by way of brainstorming. The study was conducted for 1 month starting March 24-April 23, 2021. The results showed the ranking of waste ranging from the largest to the smallest Defect of 22.70%, Overproduction of 18.32%, Inventory of 17.56%, Motion by 14.12%, Transportation of 13.10%, Waiting by 9.68% and the Process by 4.52%. The results of the waste with the largest percentage is Defect.Warehouse Raw Material di PT. XYZ menunjukkan peningkatan pada penyimpanan barang, jika tidak diimbangi dengan kinerja yang baik, maka barang yang masuk akan mengalami keterlambatan dalam penanganan. Penelitian ini bertujuan untuk mengidentifikasi pemborosan yang terjadi di Warehouse Raw Material di PT. XYZ. Fokus kajian penelitian ini adalah mengidentifikasi 7 waste yang ada di Warehouse Raw Material dengan pendekatan lean manufacturing menggunakan metode Waste Assessment Model (WAM). Proses identifikasi waste dilakukan dengan menggunakan Seven Waste Relationship, Waste Relationship Matrix (WRM) dan Waste Assessment Questionnaire (WAQ) yang kemudian di analisis menggunakan Fishbone Diagram untuk mengetahui akar penyebab masalah sehingga didapatkan usulan perbaikan yang kemudian prioritas perbaikan didapat dengan menggunkan tabel skala prioritas yang dilakukan dengan cara brainstorming. Penelitian dilakukan selama 1 bulan mulai tanggal 24 Maret-23 April 2021. Hasil penelitian menunjukkan peringkat waste mulai dari terbesar sampai terkecil yaitu Defect sebesar 22.70%, Overproduction sebesar 18.32%, Inventory sebesar 17.56%, Motion sebesar 14.12%, Transportation sebesar 13.10%, Waiting sebesar 9.68% dan Process sebesar 4.52%. Hasil waste dengan persentase terbesar adalah Defect.